Evaluasi Jalur Pedestrian Ramah Gender dengan Menggunakan Indikator Gender Impact Assestment (GIA) - Stefani Switly Peginusa; Sylviana Pelealu; Arnetha S Raintung; Dian Puspita Sari (Jurusan Teknik Sipil Politeknik Negeri Manado, 2023)
Abstract It is a must that any infrastructure built must pay attention to the aspirations, needs and problems associated with all user groups with the aim of creating a sense of security and comfort. A gender-responsive infrastructure will be considered successful if it is able to accommodate all the needs of men, women, children, the elderly, vulnerable groups equally and fairly. The existence of pedestrian paths, in addition to facilitating pedestrian access, can also be a means of city promotion which has a positive impact on improving the urban economy and reducing pollution levels due to motor vehicle exhaust emissions for better air quality. The Piere Tendean pedestrian street along the Boulevard on Business area is one of the PUPR infrastructure built by the Manado City Government. By looking at the pedestrian principle as a public space that is used for all groups, this infrastructure should have been built based on gender responsive infrastructure criteria. The evaluation was carried out using the Gender Impact Assessment (GIA) as a guide to measure the level of gender responsiveness of public works infrastructure and settlements by involving respondents from direct users of the pedestrian path. Afterwards, it was found that, in general, the pedestrian paths built did not meet the 5 (five) criteria used, so there is still a need for improvement and further development to meet gender responsive infrastructure standards. Keywords: gender responsive infrastructure, pedestrian paths, gender friendly,